2015
DOI: 10.1007/s11306-015-0796-5
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of standard lipid prediction models based on 1H-NMR spectroscopy of human serum/plasma samples

Abstract: New approaches are increasingly being used for studying and evaluating coronary heart disease (CHD), especially since the irruption of metabolomics. The classical approach is to use enzymatically-measured standard lipids and these are still the main markers for assessing risk of CHD. Since metabolomics relies on advanced analytical technologies, such as MS and NMR, using them to estimate standard lipids would be of great interest because there is no need for additional biochemical measures. The present study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“… 7 Hu analyzed the metabolic changes induced by celastrol treatment in human cervical cancer cells and provided new evidence of the pharmacological mechanism of celastrol. 8 Furthermore, some metabolic profile based discrimination models have been reported in evaluating clinical therapy, diagnosing disease, 9 revealing dose effects, 10 determining disease stage, 11 and improving avian productivity. 12 For example, a study has demonstrated the novel strategy that the metabolic profiling approach may be applicable to show the discrimination of metabolites between treated and control groups in human endothelial cells, and thus contribute to the assessment of the clinical therapeutic effect.…”
Section: Instructionmentioning
confidence: 99%
“… 7 Hu analyzed the metabolic changes induced by celastrol treatment in human cervical cancer cells and provided new evidence of the pharmacological mechanism of celastrol. 8 Furthermore, some metabolic profile based discrimination models have been reported in evaluating clinical therapy, diagnosing disease, 9 revealing dose effects, 10 determining disease stage, 11 and improving avian productivity. 12 For example, a study has demonstrated the novel strategy that the metabolic profiling approach may be applicable to show the discrimination of metabolites between treated and control groups in human endothelial cells, and thus contribute to the assessment of the clinical therapeutic effect.…”
Section: Instructionmentioning
confidence: 99%